Sorption of uranium and chromium ions on Zr/Al-pillared montmorillonite - Pylypenko, I.V.; Kovalchuk, I.A.; Kornilovych, B.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
The samples of montmorillonite pillared by polyhydroxocomplexes of zirconium and aluminum are synthesized, and the exchange of interlayer cations with the replacement of sodium cations by these polyhydroxocomplexes is confirmed by IR spectroscopy and X-ray analysis. It is shown that montmorillonite, pillared by mixed polyhydroxocomplexes, shows much higher adsorption properties in a wide range of pH concerning uranium (VI) and chromium (VI) ions in comparison with the original and modified montmorillonite with polyhydroxocomplexes of one type.